Cote d'Ivoire : Sixth Reviews Under the Arrangement Under the Extended Credit Facility and the Extended Arrangement Under the Extended Fund Facility, and Request for Extension and Augmentation of Access; Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for the Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2020)
Political uncertainty has risen ahead of the 2020 presidential elections, after the ruling coalition between President Ouattara's and former President Bedie's parties ended in the summer of 2018. The authorities have requested a one-year program extension to provide an important stability anchor through 2020. The extension will help meet balance of payment needs, foster fiscal discipline, and sustain reforms, in turn helping support the West African Economic and Monetary Union's external stability. Policies will center on preserving the program's momentum, particularly adhering to the 3 percent of GDP budget deficit ceiling, preserving a moderate risk of debt distress and fostering private sector-led growth.